Antibiotics on incidence of infection in neonates with meconium-stained amniotic fluid - M. Sholeh Kosim; N. P. Noerpramana; Asril Aminullah; Suharyo Hadisaputro (Paediatrica Indonesiana, 2013)
Background The effectiveness of antibiotics for preventinginfection in neonates with meconium-stained amniotic fluid(MSAF) remains unclear. Not all neonates with MSAF developmeconium aspiration syndrome (MAS) or neonatal infection.Furthermore, neonatal infection diagnosis may be difficult dueto lack of symptoms. As such, clinical manifestations, laboratoryresults, and infection markers are important for diagnosis.Objective To evaluate antibiotic use on the incidence ofinfectionin neonates with MSAF.Methods This double-blind randomized controlled clinical trialwas performed at Dr. Kariadi Hospital, Semarang, Indonesia fromOctober 2009 to March 2010. Subjects were newborns with MSAFwho were diagnosed by two observers (Kappa test intraobserveragreement was 0.74) and with feces metabolites found in theiramniotic fluid. Sixty-nine newborns were divided into groups Iand II, comprised of 35 and 34 subjects, respectively. Group Isubjects (control group) were not given antibiotics, while groupII subjects (treatment group) were given combination antibioticsof ampicillin (50 mg;kg BW) and gentamicin (8 mg;kg BW), assingle doses. Neonatal infection diagnosis was based on clinicalmanifestations, laboratory results (leucocyte count, blood culture,and I: T ratio), and the following infection markers: procalcitonin(PCT), interleukin-6 (IL-6), tumor necrosis tumor-a (TNF-a),and C-reactive protein (CRP). Chi-square and Fischer's exacttests were used for statistical analyses.Results We found no significant differences in the incidence ofneonatal infection between those who received and those whodid not receive antibiotics, based on clinical manifestations, thefirst and second examination of laboratory marker (P=0.53),examinations of CRP, IL-6, TNF-a, and PCT either as singlemarkers or combinations of 2, 3, or 4 markers (P> 0.05) , as wellas mortality rate (P=0.30).Conclusion There is no significant difference in the incidenceof infection in neonates with MSAF who received prophylactic antibiotics compared to those who did not receive antibiotics.